Health Information Technology Knowledge and Skills Needed by HIT Employers - Fenton, S.H.; Joost, E.; Gongora-Ferraez, M.J. (Applied Clinical Informatics, 2012)
Objective: To evaluate the health information technology (HIT) workforce knowledge and skills needed by HIT employers.Methods: Statewide face-to-face and online focus groups of identified HIT employer groups in Austin, Brownsville, College Station, Dallas, El Paso, Houston, Lubbock, San Antonio, and webinars for rural health and nursing informatics.Results: HIT employers reported needing an HIT workforce with diverse knowledge and skills ranging from basic to advanced, while covering information technology, privacy and security, clinical practice, needs assessment, contract negotiation, and many other areas. Consistent themes were that employees needed to be able to learn on the job and must possess the ability to think critically and problem solve. Many employers wanted persons with technical skills, yet also the knowledge and understanding of healthcare operations.Conclusion: The HIT employer focus groups provided valuable insight into employee skills needed in this fast-growing field. Additionally, this information will be utilized to develop a statewide HIT workforce needs assessment survey.Citation: S.H. Fenton; E. Joost; M.J. Gongora-Ferraez. Health Information Technology knowledge and skills needed by HIT employers. Appl Clin Inf 2012; 3: 448–461http://dx.doi.org/10.4338/ACI-2012-09-RA-0035
Keywords: Health information technology; workforce; biomedical and health informatics; clinical informatics